Pengaruh Disiplin Kerja terhadap Kinerja Aparatur Sipil Negara pada Dinas Pemuda Olah Raga dan Pariwisata Kabupaten Sorong Selatan - Eramury, Anitha Paula; Kastanya, James.J.; Pattiasina, Rendy. (Attractive : Innovative Education Journal, 2022)
This study aims to determine and analyze work discipline and employee performance as well as measure how much influence work discipline has on the performance of civil servants at the Department of Youth, Sports and Tourism, South Sorong Regency. The research method used is descriptive method. The subjects in this study were civil servants at the Department of Youth, Sports and Tourism, South Sorong Regency using a sample of 42 employees. The analytical technique used is simple linear regression analysis and t test with the help of SPSS 25 software to prove the effect of work discipline on employee performance. The results showed that the employee's work discipline was in the very high category and the employee's performance was in the high category. Meanwhile, based on the results of statistical tests at a significance level of 5%, the results of work discipline have a positive and significant effect on the performance of civil servants at the Youth, Sports and Tourism Office of South Sorong Regency with an R Square value of 0.559. This means that work discipline has an effect of 55.9% on employee performance, and the rest is influenced by other variables. Keywords: Work Dicipline, Employee Performance, Works Performance